Characterization of a New Pink-Fruited Tomato Mutant Results in the Identification of a Null Allele of the SlMYB12 Transcription Factor. Issue 3 (6th May 2016) - Fernandez-Moreno, Josefina-Patricia; Tzfadia, Oren; Forment, Javier; Presa, Silvia; Rogachev, Ilana; Meir, Sagit; Orzaez, Diego; Aharoni, Aspah; Granell, Antonio
Abstract : The tomato SlMYB12 transcription factor regulates flavonol glycoside biosynthesis and primary-secondary metabolism homeostasis. Abstract: The identification and characterization of new tomato ( Solanum lycopersicum ) mutants affected in fruit pigmentation and nutritional content can provide valuable insights into the underlying biology, as well as a source of new alleles for breeding programs. To date, all characterized pink-pigmented tomato fruit mutants appear to result from low SlMYB12 transcript levels in the fruit skin. Two new mutant lines displaying a pink fruit phenotype ( pf1 and pf2 ) were characterized in this study. In the pf mutants, SlMYB12 transcripts accumulated to wild-type levels but exhibited the same truncation, which resulted in the absence of the essential MYB activation domain coding region. Allelism and complementation tests revealed that both pf mutants were allelic to the y locus and showed the same recessive null allele in homozygosis: Ɗy . A set of molecular and metabolic effects, reminiscent of those observed in the Arabidopsis ( Arabidopsis thaliana ) myb11 myb12 myb111 triple mutant, were found in the tomato Ɗy mutants. To our knowledge, these have not been described previously, and our data support the idea of their being null mutants, in contrast to previously described transcriptional hypomorphic pink fruit lines. We detected a reduction in the expression of several flavonol glycosides and some associated glycosyl transferases. Transcriptome analysis further revealed that the effects of the pf mutations extended beyond the flavonoid pathway into the interface between primary and secondary metabolism. Finally, screening for Myb-binding sites in the candidate gene promoter sequences revealed that 141 of the 152 co-down-regulated genes may be direct targets of SlMYB12 regulation.